Pengaruh perasan daun cincau hijau (cyclea barbatamier) terhadap tekanan darah rata-rata (mean arterial pressure) - Zuryaty Zuryaty; mohammad lutfi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Hypertension based on mean blood pressure (mean arterial pressure) is an abnormal increase in blood pressure in arteries more than one period exceeding 70-100 mmHg. Based on the preliminary study conducted at Puskesmas Kwanyar Kabupaten Bangkalan, there were 221 people with hypertension. The objectives of the study were to analyze the effect of green rhizome leaves on mean blood pressure (mean arterial pressure) in hypertensive patients. The research design used Quasy experiment with Pretest-Postest with Control Group Design. Independent variable green jelly leaf sprinkling and dependent variable mean blood pressure (mean arterial pressure). In this study population is people who suffer from hypertension in the village of West Kwanyar work area Puskesmas Kwanyar Bangkalan district as many as 38 people. The sampling technique using Simple Random sampling. Statistical test using Paired t-test and Independent t-test with significance value α 0,05. The results showed that there was a difference of mean blood pressure (mean arterial pressure) in the treatment group with Paired t-test ρvalue 0,001 <α (0,05) and in the control group there was no difference of mean blood pressure (mean arterial pressure) with result of Paired t-test ρvalue 0,219> α (0,05). Based on the independent test t-test obtained ρvalue of 0.001 <α (0.05). Thus, there was an effect of the green jelly leaves on the mean blood pressure (mean arterial pressure). This study can be used as a source of support for further research on the benefits of green cincture leaf juice to mean blood pressure, is expected to find another alternative to lower mean blood pressure (mean arterial pressure)